Preparation method of efficient defluorination adsorbent, adsorbent obtained by preparation method and application of adsorbent

By loading Mo(OH)3-Ni(OH)2 onto porous silica particles to form a stable composite hydroxide, the problems of insufficient stability and adsorption capacity of existing defluorination adsorbents are solved, achieving a highly efficient and regenerable defluorination effect, which is suitable for the water treatment field.

CN120790091APending Publication Date: 2025-10-17BEIJING HUATEYUAN TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510703768.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-15
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing defluoridation adsorbents suffer from poor stability, low adsorption capacity, susceptibility to interference from coexisting ions, and low regeneration efficiency, making it difficult to meet drinking water standards and industrial applications.

Method used

Mo(OH)3-Ni(OH)2 was loaded onto porous silica particles, and its adsorption performance was enhanced by modification treatment. It was then regenerated in alkaline solution to form a stable composite hydroxide, thereby improving the physicochemical stability and adsorption capacity of the adsorbent.

Benefits of technology

The prepared defluoridation adsorbent has high adsorption capacity, wide pH range, and high regeneration efficiency. It can effectively reduce the concentration of fluoride ions in water to below 1 mg/L, meeting drinking water standards, and has a long service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0005596335340000011
    Figure HDA0005596335340000011
  • Figure HDA0005596335340000012
    Figure HDA0005596335340000012
Patent Text Reader

Abstract

The invention provides an efficient defluorination adsorbent preparation method, which comprises: mixing silicon dioxide powder, flour, sesbania powder and a sodium silicate aqueous solution, extruding, drying to obtain a silicon dioxide coarse material, placing in a muffle furnace, heating at a low rate, roasting for 3-6 h, dipping in a modification solution of molybdenum chloride and nickel chloride, and drying to obtain the efficient defluorination adsorbent. And then carrying out secondary modification by using an alkali solution, and drying to obtain the defluorination adsorbent. The prepared defluorination adsorbent has the adsorption capacity higher than 50 mg / g, the adsorption rate is high, the cycle performance is good, experiments prove that the fluorine ion concentration of overflowing type instantaneous produced water is smaller than 1 mg / L, and therefore the defluorination adsorbent has good water treatment performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a defluorination adsorbent, in particular to a method for preparing a highly efficient defluorination adsorbent, the defluorination adsorbent obtained by the preparation method, and application of the defluorination adsorbent in treating fluoride ions in water. Background Art

[0002] Fluoride is widely present in surface water. According to my country's "Standard for Drinking Water Quality" (GB5749-2006), the fluoride concentration limit in drinking water cannot exceed 1.0 mg L -1 Existing methods for removing fluoride from water include precipitation, ion exchange, electrodialysis, membrane separation, adsorption, and in-situ methods. Among them, adsorption is a method that uses porous materials to adsorb fluoride on the surface of solids to achieve the purpose of fluoride removal. It is a common method for removing fluoride from water and can reduce the fluoride concentration in water to 1 mg L -1 Below, it reaches the standard of drinking water, and has the advantages of being economical and simple to operate. However, existing fluorine adsorbents generally have technical defects such as poor stability, low fluorine adsorption efficiency, and low adsorption capacity. For example, Chinese invention patent application CN 117732420A discloses a sheet-like porous defluorination adsorbent, its preparation method and application. The defluorination adsorbent is a Ce-La bimetallic oxide, and the ratio of cerium to lanthanum is 4-0.5. It can complement the defluorination ability of single metal oxides (lanthanum oxide and cerium oxide), and can remove the solution fluoride ion concentration to a low level while having a large adsorption capacity. However, the preparation method uses relatively expensive rare earth metals, and the production cost is high.

[0003] Chinese invention patent application CN 112520811A discloses a manganese-loaded activated alumina defluoridation adsorbent and its preparation method. Manganese oxide is distributed on the surface of the activated alumina in the form of a protruding thorn-like structure. The manganese-loaded activated alumina particles have good porosity, a larger specific surface area, and more adsorption sites, which enhances the adsorption capacity of fluoride ions. However, this invention is only for drinking water. Similarly, Chinese invention patent application CN 116371350A discloses a preparation method for a loaded hydroxyapatite defluoridation adsorbent. The loaded hydroxyapatite defluoridation adsorbent prepared by the invention is in the shape of a thorn ball and has a hollow thorn ball structure formed by clusters of nanorods, that is, it has a larger specific surface area, and the defluoridation efficiency and adsorption capacity are significantly improved. However, this method does not have a clear reproducible method.

[0004] Through analysis of existing technologies, it was found that existing fluorine removal adsorbents generally have the disadvantages of low adsorption capacity and susceptibility to interference from coexisting ions, or are difficult to apply industrially due to problems such as limited pH range and low regeneration efficiency. Summary of the Invention

[0005] The present application aims to overcome the disadvantages of the prior art, and provide a defluorination adsorbent with stable physical and chemical structure, high adsorption capacity, high regeneration efficiency and long service life.

[0006] The idea of the present application is to load Mo(OH)3-Ni(OH)2 on porous silica particles, so as to improve the adsorption capacity of the porous silica by Mo(OH)3-Ni(OH)2, thereby widening the application range and improving the regeneration efficiency.

[0007] Based on this, the present application provides a preparation method of a high-efficiency defluorination adsorbent, which comprises the following steps:

[0008] (1) Preparation of silica raw material

[0009] Silica powder, flour and sesbania powder are weighed according to the weight ratio of 100-120:10-18:2-20, uniformly mixed to obtain a composite powder, and then 10%-80% sodium silicate aqueous solution is added to the composite powder at 120-200% of the total weight of the composite powder, and the mixture is uniformly mixed and then placed in a molding equipment for extrusion molding to obtain a wet material, which is dried at 100-150°C to obtain a silica raw material;

[0010] (2) Preparation of porous silica carrier

[0011] The silica raw material obtained in step (1) is cut into granular substrates with an average particle size of 1-2 mm by a mechanical method, and then placed in a muffle furnace and heated at a rate of 2-10°C / min to 500-1000°C, and held at a constant temperature for 3-6h to obtain a porous silica carrier;

[0012] (3) Loading

[0013] Molybdenum chloride and nickel chloride are weighed according to a molar ratio of 3-8:7-2, and then added to deionized water and stirred until completely dissolved to prepare a modified solution with a concentration of 0.1-2 mol / l, 1-1.5 times the volume of the modified solution and the porous silica carrier are taken, and the carrier is fully immersed in the modified solution, and then dried at 100-150°C to obtain a first modified material;

[0014] (4) Post-treatment

[0015] A sodium hydroxide or KOH aqueous solution with a concentration of 0.5-2 mol / l is prepared to obtain a secondary modified solution, 1.0-1.5 times the secondary modified solution and the first modified material are taken, and the first modified material is fully immersed in the secondary modified solution, and then dried at 110-150°C to obtain a defluorination adsorbent.

[0016] In the present application, the average particle size of the silica powder in step (1) is 100-1000 mesh

[0017] The average particle size of the rice powder in step (1) is in the range of 100-1000 mesh.

[0018] In the present application, during the extrusion process in step (1), the rice powder plays a role in material lubrication, which is beneficial to the extrusion molding of wet materials; on the other hand, when calcination is carried out in step (2), the rice powder will be burned off during the calcination process, thereby forming channels in the porous silica carrier and increasing the specific surface area of the porous silica carrier, thereby improving the adsorption performance of the fluorine adsorbent.

[0019] As a preferred embodiment, the drying in step (1) is drying at 100-150°C for 24-48h.

[0020] And the drying in steps (3) and (4) is usually drying at 100-150°C for 12-24h.

[0021] Further, the present application also provides the application of the defluorination adsorbent obtained by the above preparation method in removing fluorine ions in water, which is particularly beneficial in the environment where the concentration of fluorine ions in water is <150ppm.

[0022] The present application uses the characteristics of large specific surface area and good stability of silica as the main raw material for preparing the carrier. Since silica is non-toxic and harmless and will not cause secondary pollution to the environment, the selection of silica as the adsorbent carrier meets the environmental protection requirements.

[0023] The present application combines two elements of molybdenum and nickel, and uniformly distributes the molybdenum-nickel composite hydroxide Mo(OH)3-Ni(OH)2 on the surface of the porous silica, thereby increasing the defluorination effect of the adsorbent. After the modified carrier is soaked in alkali solution, it is beneficial to more firmly fixing the two kinds of hydroxides loaded on the silica substrate, so that the effective substances will not fall off during the engineering application, and the running stability is more excellent.

[0024] The porous defluorination agent in the present application has high adsorption capacity, is suitable for the treatment of various fluorine-containing wastewater, makes the fluorine ion concentration of the produced water <1mg / L, meets the "Drinking Water Health Standards" GB5749-2022, has a fast adsorption rate, and has a simple regeneration method and good recycling performance. BRIEF DESCRIPTION OF DRAWINGS Fig. 1 The surface morphology observation results of the porous silica carrier of Example 1 and Sample 1; Fig. 2 The surface morphology observation results of the porous silica carrier of Example 2 and Sample 2. DETAILED DESCRIPTION

[0025] The following examples are used to non-limitingly explain the technical solutions of the present application.

[0026] In the present application, unless otherwise specified, the concentration "%" used for illustration is weight percent, and ":" is weight ratio.

[0027] Example 1

[0028] The 200-mesh silica powder, flour and sesbania powder were mixed uniformly at a mass ratio of 100:10:10, and a 30% sodium silicate aqueous solution was uniformly sprayed on the mixed powder, with a mass (or volume ratio) of the sodium silicate aqueous solution to the mixed powder of 120%. Then the silica powder was extruded into a strip-shaped body using an extruder at 20 rpm, and was placed in a 100°C oven for drying for 48 h to obtain a shaped silica. The obtained shaped silica was cut into short filament strip-shaped bodies of 1-2 mm using a mechanical cutter, and finally was placed in a muffle furnace, and was heated at a rate of 2°C / min to 500°C, and was annealed at a constant temperature for 3 h to obtain a porous silica carrier.

[0029] Then, molybdenum chloride and nickel chloride were placed in a 1L beaker at a molar ratio of 3:7, and deionized water was added and stirred until completely dissolved to obtain a modified solution with a mixed concentration of 1 mol / L. One volume part of the porous silica carrier was immersed in 1 volume part of the solution, and was taken out after standing for 2 h, and was placed in a 100°C oven for drying for 12 h. Then, a 1 mol / L sodium hydroxide solution was prepared, and the dried silica carrier that had been immersed in the molybdenum chloride and nickel chloride was again immersed in an equal volume of the sodium hydroxide solution uniformly, and was allowed to stand for 2 h, and was placed in a 110°C oven for drying for 12 h to obtain an adsorbent sample 1.

[0030] Example 2

[0031] A porous silica carrier was prepared by extrusion molding using 200-mesh silica powder as a raw material and sodium silicate as a binder. First, the silica powder, flour and sesbania powder were mixed uniformly at a mass ratio of 120:18:2, and a 50% sodium silicate aqueous solution was uniformly sprayed on the mixed powder until the powder was in a plastic state. Then the silica powder was extruded into a strip-shaped body using an extruder at 80 rpm, and was placed in a 130°C oven for drying for 24 h to obtain a shaped silica. The obtained shaped silica was cut into short filament strip-shaped bodies of 1-2 mm using a mechanical cutter, and finally was placed in a muffle furnace, and was heated at a rate of 5°C / min to 800°C, and was annealed at a constant temperature for 3 h to obtain a porous silica carrier.

[0032] Molybdenum chloride and nickel chloride were placed in a 1 L beaker in a molar ratio of 5:5, deionized water was added and stirred until completely dissolved to obtain a modified solution with a mixed concentration of 1.2 mol / L. Impregnation was performed on the porous silica carrier prepared above according to 1.5 times the volume, and after standing for 2 h, it was placed in a 120°C oven for drying for 12 h; then a 1.5 mol / l sodium hydroxide solution was prepared, and the porous silica carrier impregnated with molybdenum chloride and nickel chloride above was again impregnated with an equal volume of the solution, and after standing for 2 h, it was placed in a 120°C oven for drying for 12 h to obtain fluoride removal adsorbent sample 2.

[0033] Example 3 (Comparative Example 1)

[0034] The porous silica carrier was prepared as in Example 1.

[0035] Then, molybdenum chloride and nickel chloride were placed in a 1 L beaker in a molar ratio of 2:8, deionized water was added and stirred until completely dissolved to obtain a modified solution with a mixed concentration of 1 mol / L. Impregnation was performed on the porous silica carrier prepared above according to an equal volume, and after standing for 2 h, it was placed in a 100°C oven for drying for 12 h; then a 1 mol / l sodium hydroxide solution was prepared, and the porous silica carrier impregnated with molybdenum chloride and nickel chloride above was again impregnated with an equal volume of the solution, and after standing for 2 h, it was placed in a 110°C oven for drying for 12 h to obtain fluoride removal adsorbent sample 3.

[0036] Example 4 (Comparative Example 2)

[0037] The porous silica carrier was prepared as in Example 1.

[0038] Molybdenum chloride and nickel chloride were placed in a 1 L beaker in a molar ratio of 1:9, deionized water was added and stirred until completely dissolved to obtain a modified solution with a mixed concentration of 1.2 mol / L. Impregnation was performed on the porous silica carrier prepared above according to 1.5 times the volume, and after standing for 2 h, it was placed in a 100°C oven for drying for 12 h; then a 1 mol / l sodium hydroxide solution was prepared, and the porous silica carrier impregnated with molybdenum chloride and nickel chloride above was again impregnated with an equal volume of the solution, and after standing for 2 h, it was placed in a 110°C oven for drying for 12 h to obtain fluoride removal adsorbent sample 4.

[0039] Surface morphology observation: The morphology of samples 1 and 2 was observed as shown in Figs. 1-2 .

[0040] Adsorption performance test

[0041] Take 10g of each fluoride removal adsorbent sample, 5L of fluoride ion test solution (F-theoretical concentration is 100mg / L, pH=6), adsorb at room temperature, then use a syringe to suck the solution, test the F-concentration of the obtained water sample using ion chromatography analysis system (ICS). Calculate the mass adsorption capacity Q.

[0042] Adsorbent cycle regeneration test

[0043] Take the adsorbed adsorbent sample, immerse it in a 1mol / L NaOH solution, take it out after 5h of immersion, wash the adsorbent with pure water several times until the solution TDS<20mg / L, then put the regenerated adsorbent into a 60℃ oven for drying. The test results are as shown in Table 1:

[0044] Table 1

[0045]

[0046] The fluoride removal adsorbents prepared in Examples 1 and 2 in Table 1 have high adsorption capacity, all above 50mg / g, fast adsorption rate and good cycle performance. The two competitive mesoporous alumina and calcium-aluminum-lanthanum composite adsorbents selected from the market have lower adsorption performance, slower adsorption rate, and obvious cycle performance decay.

[0047] In addition, the molybdenum-nickel composite hydroxide fluoride removal adsorbents prepared in Examples 1 and 2 have a fluorine ion concentration of less than 1mg / L in the overflow type instantaneous water production, meeting the GB5749-2022 "Drinking Water Health Standards", while the fluorine ion concentration of the two competitive mesoporous alumina and calcium-aluminum-lanthanum composite adsorbents selected from the market is more than 1mg / L in the overflow type instantaneous water production, which cannot meet the GB5749-2022 "Drinking Water Health Standards". Therefore, the molybdenum-nickel composite hydroxide fluoride removal adsorbents prepared in the present application are suitable for the field of water treatment technology and have better performance than the prior art.

Claims

1. A method for preparing a high-efficiency defluorination adsorbent, comprising the following steps: (1) Preparation of crude silicon dioxide material Silica powder, flour, and sesbania powder are weighed in a weight ratio of 100-120:10-18:2-20, and mixed uniformly to obtain a composite powder; a sodium silicate aqueous solution having a mass concentration of 10%-80% is added based on 120-200% of the total weight of the composite powder; the mixture is placed in a molding device and extruded to obtain a wet material; and the obtained wet material is dried at 100-150° C. to obtain a crude silica material; (2) Preparation of porous silica carrier The silica crude material obtained in step (1) is mechanically cut into a granular substrate with an average particle size of 1-2 mm, and then placed in a muffle furnace, heated to 500-1000° C. at a rate of 2-10° C. / min, and calcined at a constant temperature for 3-6 hours to obtain a porous silica carrier; (3) Load Molybdenum chloride and nickel chloride are weighed in a molar ratio of 3-8:7-2, and deionized water is added and stirred until completely dissolved to prepare a modified solution with a concentration of 0.1-2 mol / l. 1-1.5 times the volume of the modified solution and a porous silica support are taken, and the support is fully immersed in the modified solution, and then dried at 100-150°C to obtain a primary modified material; (4) Post-processing A sodium hydroxide or KOH aqueous solution with a concentration of 0.5-2 mol / l is prepared to obtain a secondary modified solution, 1-1.5 times the volume of the secondary modified solution and the primary modified material are taken, the primary modified material is fully immersed in the secondary modified solution, and then dried at 110-150°C to obtain a defluorination adsorbent.

2. The method for preparing a high-efficiency defluorination adsorbent according to claim 1, wherein The average particle size of the silicon dioxide powder in step (1) is 100-1000 mesh.

3. The method for preparing a high-efficiency defluorination adsorbent according to claim 1, characterized in that The average particle size of the sesbania powder in step (1) is 100-1000 mesh.

4. The method for preparing a high-efficiency defluorination adsorbent according to claim 1, wherein The drying in step (1) is carried out at 100-150° C. for 24-48 hours.

5. The method for preparing a fluorine adsorbent according to claim 1, characterized in that The drying in steps (3) and (4) is carried out at 100-150° C. for 12-24 hours.

6. Use of the high-efficiency defluorination adsorbent obtained by the preparation method according to any one of claims 1 to 5 in removing fluoride ions from water.

7. The use according to claim 6, characterized in that The concentration of fluoride ions in water is <150 ppm.

Citation Information

Patent Citations

  • Manganese-loaded activated aluminum oxide defluorination adsorbent and preparation method thereof

    CN112520811A

  • Preparation method of hydroxyapatite-loaded defluorination adsorbent and defluorination adsorbent

    CN116371350A

  • Flaky porous defluorination adsorbent as well as preparation method and application thereof

    CN117732420A